2018
DOI: 10.1016/j.micres.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for up and down regulation of 450 genes by rpoB12 (rif) mutation and their implications in complexity of transcription modulation in Escherichia coli

Abstract: Analyses of mutations in rpoB subunit of Escherichia coli that lead to resistance to rifampicin have been invaluable in providing insight into events during transcription continue to be discovered. Earlier we reported that rpoB12 suppresses over-expression of cps genes in Δlon mutant of E. coli, by interfering with the transcription of rcsA. Here we report Microarray based Transcriptome profile of Δlon and Δlon rpoB12 strains. The data analyses clearly reveal that rpoB12 mutation results in the differential ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Since rpoB alleles confer changes to cellular physiology and gene expression in a global sense ( Conrad et al, 2010a ), we tested how the three rpoB alleles change the ability of E. coli to swim in liquid media. Alleles of rpoB have previously been shown to lead to a decrease in the gene expression of genes associated with flagellar biosynthesis, and as a result, reduced motility on plates ( Conrad et al, 2010a ; Meenakshi and Munavar, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since rpoB alleles confer changes to cellular physiology and gene expression in a global sense ( Conrad et al, 2010a ), we tested how the three rpoB alleles change the ability of E. coli to swim in liquid media. Alleles of rpoB have previously been shown to lead to a decrease in the gene expression of genes associated with flagellar biosynthesis, and as a result, reduced motility on plates ( Conrad et al, 2010a ; Meenakshi and Munavar, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, microarray-based transcriptome profiling of rpoB12 mutants indicated that certain genes coding for sRNAs were also modulated. For example, the expression of sRNA genes (including ryhB , gadY , glmY , isrB , rydC , ryjA, sokB , csrC , and rye ) was up- or downregulated in the presence of rifampicin . It is possible that mutations in rpoB may cause expression changes of sRNA genes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the expression of sRNA genes (including ryhB, gadY, glmY, isrB, rydC, ryjA, sokB, csrC, and rye) was up-or downregulated in the presence of rifampicin. 90 It is possible that mutations in rpoB may cause expression changes of sRNA genes. In this study, the transcriptional level of sRNA SgrS was downregulated, while that of ArrS was upregulated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Overnight grown cultures of SG20780 (∆ lon cps-lac ) and MMR6 (∆ lon cps-lac rpoB12 ) were sub-cultured in duplicates and the mid-log phase cultures were used for the microarray experiment. Refer [2] for more details.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“… Data source location Tamil Nadu, India. Data accessibility Data are available in this article Related research article “Evidence for Up and Down Regulation of 450 genes by rpoB12 (rif) Mutation and their Implications in Complexity of Transcription Modulation in Escherichia coli” [2] . …”
Section: Specifications Tablementioning
confidence: 99%